Farmers' Satisfaction with the Implementation of Certified Rice Seed Breeding in Batanghari Regency - Nurmansyah, Ilham; Muchlis, Fuad; Kurniasih, Siti (JALOW | Journal of Agribusiness and Local Wisdom, 2025)
This shows that the supply of rice seeds in Jambi Province is insufficient. Pemayung District has 19 villages, but only 9 villages cultivate paddy fields. Senaning Village and Lubuk Ruso Village are the villages with the highest productivity levels of 6.25 tons/ha and 5.75 tons/ha. Factors related to the provision of seeds include the management, management and use of agricultural tools and machinery in Senaning and Lubuk Ruso Villages. This study aims to describe farmers' satisfaction with paddy rice seed breeding technology. Analysis method used is descriptive statistical data. Primary data was collected using a questionnaire and with a sample of 35 respondents. The results of the study revealed that farmers' satisfaction with certified rice seed breeding techniques was included in the category of satisfaction in the expectation indicator of 71% and farmer satisfaction in the performance indicator of 54%. This shows that all the sample farmers are satisfied with the results obtained from certified rice seeds. The implementation of breeding paddy rice seeds in Senaning Village, Pemayung District, Batanghari Regency is in the high category of 60% and in accordance with the Operational Standards Procedures of the West Java Agricultural Technology Assessment Center (BPTP). Conclusion: Farmers' satisfaction in cultivating local rice farming is included in the satisfied category for expectations and performance indicators and the implementation of paddy rice seed breeding in Senaning Village, Pemayung District, Batanghari Regency is in the high category in accordance with the SOP of the Agricultural Technology Assessment Center.